COMPLEX MODIFICATION OF SECONDARY SILUMINS - Mityayev, A. A.; Volchok, I. P.; Frolov, R. A.; Loza, K. N.; Hnatenko, O. V.; Lukinov, V. V. (Science and Transport Progress, 2014)
Purpose. Development of scientific and technological bases of formation of the specified secondary hypoeutectic (АK8M3) and eutectic (АК12М2MgН) silumins’ structure; and increasing their mechanical and service properties’ indices in the cast state and after heat treatment up to the level of primary alloys. Methodology. Determination of the chemical composition was conducted by spectral analysis on the spark spectrometer «SPECTROLAB» (Germany). Metallographic analysis was performed on the microscopes МIМ-7 and МIМ-8, and also by the high definition metallography method using the raster electronic microscope «JSMT-300» (Japan). Heat treatment of aluminum alloys was carried out applying T1 and T5 modes according to State Standard of Ukraine 2839-94 (GOST 1583-93). Standard techniques were used during the determination of mechanical properties. The temperature coefficient of linear expansion for the piston alloy АK12М2МgH (AL25) was determined using the specimens Ø with the diameter of 3.5 mm and length of 50 mm with the use of Shevenard optical quartz dilatometer. High temperature fracture resistance was determined according to State Standard 10145-81 as the time before fracture of the specimen at specified stress of 50 MPa and temperature of 300°С. Findings. The technology of obtaining alloys from charge, which consists of 100 % scrap and production wastes has been developed and implemented into production. This technology provides obtaining of metal of the guaranteed chemical composition and high quality with the reduction of energy costs for melting. Originality. The regularities of the formation of the structural and phase state and the level of physical and mechanical properties of eutectic and secondary hypoeutectic silumins depending on the refining and modifying processes have been established. The generalization of regularities of the secondary silumins’ fracture has been carried out. Quantitative characteristics of the intermetallic phases’ role in the fracture mechanisms and aluminum alloys’ mechanical properties level formation have been obtained. Practical value. Structure formation processes of secondary aluminium alloys depending on their production technology have been studied. Highly efficient refining and modifying complexes for treatment of secondary hypoeutectic and eutectic aluminum alloys have been developed and the optimal quantity of modifiers depending on the charge quality has been determined.